2005
DOI: 10.1523/jneurosci.2010-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Two Isoforms of theCaenorhabditis elegansLeukocyte-Common Antigen Related Receptor Tyrosine Phosphatase PTP-3 Function Independently in Axon Guidance and Synapse Formation

Abstract: Leukocyte-common antigen related (LAR)-like phosphatase receptors are conserved cell adhesion molecules that function in multiple developmental processes. The Caenorhabditis elegans ptp-3 gene encodes two LAR family isoforms that differ in the extracellular domain. We show here that the long isoform, PTP-3A, localizes specifically at synapses and that the short isoform, PTP-3B, is extrasynaptic. Mutations in ptp-3 cause defects in axon guidance that can be rescued by PTP-3B but not by PTP-3A. Mutations that sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
146
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(161 citation statements)
references
References 48 publications
15
146
0
Order By: Relevance
“…In addition, for the possible functional link between SYD-2, LAR and Nidogen, reports indicated that SYD-2 might recruit other density components to facilitate its assemble, and the presynaptic activity of SYD-2 might be modulated by LAR-Nidofen interaction to secure the synaptic assembly [21,22] . HLB-1/ liprinβ1 motif also suggested that HLB-1/ liprinβ1 might encode another scaffold protein at synaptic since it had a similar SAM domain as that in SYD-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for the possible functional link between SYD-2, LAR and Nidogen, reports indicated that SYD-2 might recruit other density components to facilitate its assemble, and the presynaptic activity of SYD-2 might be modulated by LAR-Nidofen interaction to secure the synaptic assembly [21,22] . HLB-1/ liprinβ1 motif also suggested that HLB-1/ liprinβ1 might encode another scaffold protein at synaptic since it had a similar SAM domain as that in SYD-2.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of SNB-1::GFP, UNC-49::GFP and UNC-10 expressions was performed as described [20][21][22] .…”
Section: Microscopy and Quantificationmentioning
confidence: 99%
“…In C. elegans syd-2 mutants, the LAR homologue PTP-3 fails to cluster at synapses (24), and in cultured mammalian cells, Liprin-␣ promotes the localization of LAR to focal adhesions (18,23). We therefore analyzed the intracellular distribution of LAR in Liprin-␣ oos mutant photoreceptors.…”
Section: Liprin-␣ Is Not Required For Lar Localization In Photoreceptmentioning
confidence: 99%
“…In cultured hippocampal neurons, Liprin-␣ promotes glutamate receptor targeting to synapses (21,22). The observations that human Liprin-␣2 promotes clustering of LAR within the plasma membrane in COS cells, and that SYD-2 and the C. elegans LAR homologue PTP-3 regulate each other's localization along the nerve cord, suggest that localization also may be the mechanism by which Liprin-␣ influences LAR function (23,24).…”
mentioning
confidence: 99%
“…Mutant analyses in C. elegans and Drosophila melanogaster have led to identification of a number of active zone molecules important for presynaptic development and function. For example, SYD-2 (liprin-α) or LAR mutants exhibit elongated and irregular active zones in neuromuscular junctions of worms and flies [15][16][17] . Bruchpilot, another scaffolding molecule, which is the D. melanogaster homolog of ELKS-1 (ERC or CAST), was recently shown to be important for formation of T-bars and localization of calcium channels at the neuromuscular junction 18,19 .…”
mentioning
confidence: 99%